2018
DOI: 10.1186/s40164-018-0102-0
|View full text |Cite
|
Sign up to set email alerts
|

An integrated view of the role of miR-130b/301b miRNA cluster in prostate cancer

Abstract: Prostate cancer is a major health problem worldwide due to its high incidence morbidity and mortality. There is currently a need of improved biomarkers, capable to distinguish mild versus aggressive forms of the disease, and thus guide therapeutic decisions. Although miRNAs deregulated in cancer represent exciting candidates as biomarkers, its scientific literature is frequently fragmented in dispersed studies. This problem is aggravated for miRNAs belonging to miRNA gene clusters with shared target genes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 71 publications
3
43
0
Order By: Relevance
“…(29) However, recently it was reported to be linked to bone metabolism in ovariectomized rats, (30) and TargetScan also predicts it to interact directly with several bone-related proteins, such as WNT1, LRP6, and PTEN. Furthermore, miR-301b belongs to the miR-130 gene family together with miR-130b, miR-301a, and miR-130a, (31) which in turn have been reported to partake in osteogenesis and chondrogenesis. (32,33) Last, Liu and colleagues (34) have reported that expression of miR-301b-3p in bone marrow correlates with adipogenic potential of mesenchymal stem cells (MSCs).…”
Section: Discussionmentioning
confidence: 99%
“…(29) However, recently it was reported to be linked to bone metabolism in ovariectomized rats, (30) and TargetScan also predicts it to interact directly with several bone-related proteins, such as WNT1, LRP6, and PTEN. Furthermore, miR-301b belongs to the miR-130 gene family together with miR-130b, miR-301a, and miR-130a, (31) which in turn have been reported to partake in osteogenesis and chondrogenesis. (32,33) Last, Liu and colleagues (34) have reported that expression of miR-301b-3p in bone marrow correlates with adipogenic potential of mesenchymal stem cells (MSCs).…”
Section: Discussionmentioning
confidence: 99%
“…As described above, miR‐130b packaged in exosomes from prostate cancer cells play a role in ASC‐prostate tumor crosstalk . Additionally, exosomes derived from bone marrow‐derived mesenchymal stem cells promote tumor growth of gastric carcinoma cell line SCG‐7901 .…”
Section: Influential Pathways In Ascs and Cancermentioning
confidence: 94%
“…Upon priming with PCa conditioned media or PCa derived exosomes, ASCs form prostate‐like neoplastic lesions in vivo and aggressive tumors in secondary recipients . PCa derived exosomes, containing miR‐130b, induce ASC neoplastic reprogramming through upregulation of hRAS and kRAS, and the downregulation of the tumor suppressor gene programmed cell death protein 4 .…”
Section: Ascs In Cancermentioning
confidence: 99%
“…The list of miRNAs that are related with prostate cancer is long; for example, Elnaz Pashaei et al conducted a meta-analysis, including 37 microRNAs, of which 15 over expressed and 22 under expressed in prostate cancer [44]. Of these, only the following microRNAs were correlated with prostate cancer: miR-1 [45,46], miR-133b [47], miR-449a [48], miR-137 [49], miR-370 [50], miR-221 [51], miR-449b [35], miR-125a-5p [52], miR-199a-3p [53], miR-301b [38], miR-340 [39], miR-361 [40], miR-363 [54], miR-98 [55]. MiR-1, miR-133B, miR-449B and miR-221 were reported with significant value in prostate cancer prediction after radical prostatectomy.…”
Section: Mirnas Signature In the Diagnosis Of Prostate Cancermentioning
confidence: 99%
“…MiR-130b/miR-301b cluster was found to be up-regulated in prostate cancer. Their oncogenic role was determined by a complex analysis of patient cohort samples correlated with gene expression data [38]. Moreover, miR-301b-3p is an important target since hypoxia, a very common phenomenon [87], will enhance its expression level in prostate cancer [88].…”
Section: Mirnas Therapeutic Role In Prostate Cancermentioning
confidence: 99%